2019
DOI: 10.1021/acs.orglett.9b03539
|View full text |Cite
|
Sign up to set email alerts
|

Daphneodorins A–C, Anti-HIV Gnidimacrin Related Macrocyclic Daphnane Orthoesters from Daphne odora

Abstract: Three novel gnidimacrin related macrocyclic daphnanes (GMDs), daphneodorins A-C (2-4), were isolated from Daphne odora Thunb., together with gnidimacrin (1). Their structures were established by extensive physicochemical and spectroscopic analyses. Compounds 2 and 3 potently inhibited HIV-1 replication at subnanomolar concentrations (EC 50 0.16 and 0.25 nM, respectively). Compounds 2-4 represent a novel type of GMDs that are highly oxygenated on the macrocyclic ring, suggesting good potential for anti-HIV drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
3
20
0
2
Order By: Relevance
“…In the macrocyclic ring part, the NOESY correlation between H 3 -10′/H-2 and H 3 -10′/H-10 suggested that CH 3 -10' has the β-orientation. The chemical shift of CH 3 -10′ in 1 (δ C 13.0) was also in good agreement with the previously reported value when it was β-orientation[3][4][5]16], whereas the CH 3 -10' epimer of 1, genkwadane B, was reported at δ C 19.0[17].Four peaks (3, 4, 6, and 7) detected in the LC-MS analysis could not be isolated, and their structures were deduced by the information of molecular formula, retention time, and MS/MS fragmentation pattern. Peak 6 was identified as gnidimacrin by comparison with the standard compound.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…In the macrocyclic ring part, the NOESY correlation between H 3 -10′/H-2 and H 3 -10′/H-10 suggested that CH 3 -10' has the β-orientation. The chemical shift of CH 3 -10′ in 1 (δ C 13.0) was also in good agreement with the previously reported value when it was β-orientation[3][4][5]16], whereas the CH 3 -10' epimer of 1, genkwadane B, was reported at δ C 19.0[17].Four peaks (3, 4, 6, and 7) detected in the LC-MS analysis could not be isolated, and their structures were deduced by the information of molecular formula, retention time, and MS/MS fragmentation pattern. Peak 6 was identified as gnidimacrin by comparison with the standard compound.…”
supporting
confidence: 92%
“…Although weaker than the positive control, gnidimacrin (6), they still showed potent anti-HIV activity, of which compounds 1, 2 and 8 with IC 50 < 1 nM. The MDOs 2 (IC 50 0.44 nM) and 6 (IC 50 0.08 nM) exhibited more potent activity than 1 (IC 50 0.99 nM) and 5 (IC 50 3.61 nM), suggesting that the benzoyl group at C-3 is favorable for anti-HIV activity than at C-20 [5,12]. As for nonmacrocyclic daphnanes (8, IC 50 0.69 nM versus 9, IC 50 5.86 nM), a saturated aliphatic chain which attached at C-1′ was favorable for anti-HIV activity than the unsaturated aliphatic chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 In particular, gnidimacrin potently inhibited HIV-1 replication in assays of HIV replication, which was 5000-and 500-fold greater than the inhibition induced by prostratin and the HIV-1 antiretroviral drug zidovudine (AZT), respectively. 8 Such results encourage the investigation of various tigliane and daphnane diterpenes as novel anti-HIV agents for research and clinical studies.…”
mentioning
confidence: 94%